PEMLIF—a tale of two stories - Kutty, Raja K.; Sunilkumar, Balakrishnan Sreemathyamma; Peethambaran, Anilkumar; Jain, Sourabh Kumar; Kumar, Shailesh (Journal of Spine Surgery; Vol 3, No 3 (September 29, 2017): Journal of Spine Surgery, 2017)
Intervertebral disc prolapse is a common cause of both acute and chronic low back pain. This can result in differential grades of motor and sensory disturbances in lower limbs and even cauda equina syndrome (CES). The neurological manifestations are a result of compression of the spinal cord and roots ventrally in the spinal canal due to the prolapsed disc. However, neurologic deficits owing to compression of the spinal cord dorsally as a result of migration of sequestrated disc fragments are very rare. We present two different cases of back pain with severe neurologic deficit referred to us within a short span of one month. Among them, one had long standing history of back pain while other had none. Both patients were investigated and found to have a sequestrated disc fragment which had dorsally migrated to the epidural space and was causing severe compression of the spinal cord. They underwent laminectomy and removal of the sequestrated fragment. However, they were only partially relieved of their motor and bladder weakness. We present our cases to highlight this rare form of lumbar epidural intervertebral disc migration, as well as enumerate the diagnostic challenges and discuss the differential diagnosis and treatment.